Cameroon : Poverty Reduction Strategy Paper Third Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2006)
The Annual Progress Report for Cameroon assesses the major achievements of the Poverty Reduction Strategy Paper under the staff-monitored program (SMP). It highlights the coherence in government action, the introduction of administrative management in strategic programming and planning tools, and effectiveness in the use of human, material, and financial resources. To solve the existing problems, beneficiaries had made recommendations to improve the quality of projects. The second generation PRSP was aimed at reinforcing the growth strategy and the mobilization of foreign aid through intensive use of budgetary aid.